Desire and Imitation in International Politics - Troy, Jodok (Book collections on Project MUSE., 2021)
"Imitating the desire of others is inherent to the struggle for power in international politics. The imitation of desire is a human trait seldom recognized in International Relations studies, let alone conceptualized. The imitation of desire that takes place among entities--as opposed to being intentionally generated by them--challenges the conventional wisdom of International Relations that assumes rational autonomous individuals. This book identifies the root of Realism, pointing out its awareness of the conflicting impact of desire and imitation in a world driven by restless comparison. It subsequently demonstrates the conceptual value of mimetic theory while proposing a template of understanding international polities, starting from assumptions of disorder and violence. This volume not only contributes to the study of conflict based on the imitation of the desire of others among international polities but also proposes in its conceptualization that it is worth looking at studies of agency and structure, normative change, peace, and reconciliation."--Front flap of paper wrapper.